Production of Biofuel by Hydrocracking of Cerbera Manghas Oil Using Co-Ni/HZSM-5 Catalyst : Effect of Reaction Temperature - Lenny Marlinda; Muhammad Al Muttaqii; Achmad Roesyadi; Danawati Hari Prajitno (Chemistry Department, The University of Brawijaya, 2016)
This research aims to investigate the effect of various reaction temperatures on the hydrocracking of Cerbera manghas oil to produce biofuel as a paraffin-rich mixture of hydrocarbons with Co-Ni/HZSM-5 catalyst. Co-Ni/HZSM-5 catalyst was prepared by incipient wetness impregnation. The catalyst was characterized by X-ray diffraction (XRD), N2 physisorption according to the Brunauer-Emmet-Teller (BET) method, and atomic absorption spectrometry (AAS). The hydrocracking reaction was carried out in a pressure batch reactor, reaction temperatures of 300-375 oC for 2 hours, reactor pressure of 15 bar after flowing H2 for at least 1 hour, and a catalyst/oil ratio of 1 g/200 ml. The hydrocarbon composition was determined by gas chromatography-mass spectrometry (GC-MS). With the Co(0.88%)-Ni(3.92%)/HZSM-5 catalyst, the highest yield for gasoil was 46.45% at temperature of 350 oC. At this reaction temperature condition, the main abundant hydrocarbon compounds in gasoil-like hydrocarbon were n-paraffin, i.e. pentadecane of 20.06 area% and heptadecane of 14.13 area%. Biofuels produced showed that abundant hydrocarbon compounds were different at different reaction temperatures. Iso-paraffin with low freezing point and good flow property were not found in gasoil-like hydrocarbon. Isomerization depends on reaction condition and type of catalyst.